Curvilinear telomere length dynamics in a squamate reptile. (17th October 2016) - Ujvari, Beata; Biro, Peter A.; Charters, Jordan E.; Brown, Gregory; Heasman, Kim; Beckmann, Christa; Madsen, Thomas
Summary: The lack of consensus concerning the impact of telomere length (TL) dynamics on survival emphasizes the need for additional studies to evaluate the effect of TL on key life‐history processes. Using both cross‐sectional and longitudinal data, we therefore explored age‐specific TL dynamics in a squamate reptile: the frillneck lizard ( Chlamydosaurus kingii ). Our cross‐sectional analyses revealed that young lizards had short TL, TL increased in medium‐aged lizards, but TL decreased in older age cohorts, revealing a curvilinear relationship between TL and frillneck lizard age. Neither our cross‐sectional nor our longitudinal analyses revealed any association between TL dynamics and lizard survival. We observed a significant positive relationship between TL and telomerase expression (TE), suggesting that TE is a significant determinant of frillneck lizard TL dynamics. Importantly, our longitudinal analyses revealed a positive relationship between initial TL and telomere attrition rate within individual lizards, that is lizards with short initial telomeres were subjected to reduced telomere attrition rates compared to lizards with long initial TL. Our results strongly suggest that TL and TE dynamics in frillneck lizards is not associated with lizard survival but rather reflect an adaptation to maintain TL above a critical minimum length in order to sustain cellular homeostasis. A lay summary is available for this article. Abstract : Lay Summary